Automation of Stump and Stem Analysis - Sharma, Uttam Kumar; Chandiwal, Mayank; Garg, Naveen; Goyal, Punit; Chouhan, Amit; Gupta, Sidhartha (Indian Forester, 2018)
Measurement of growth of an individual tree forms the basis of measurement of growth/increment of forest and ultimately, management of forest. For trees showing annual rings, growth relationship i.e. growth of breast height diameter, height and volume with age require analysis of the whole stem of the tree known as ’Stem Analysis’. Growth of breast height diameter with age can be found by ’Stump Analysis’ also. During this analysis, data are collected from of trees/stumps in the field and then collected data is analysed. A computer/mobile based program in which the field data can directly be entered and all computation including graph plotting will be done by computer/mobile, is always desirable for those field foresters who are involved in Mensuration exercise. Considering the utility of such application in mind, a computer software program in MS Excel and a mobile based application have been developed for Stem and Stump Analysis. Both the applications have been checked with data collected for Cedrus deodara at Kanasar, Chakrata Forest Division, Dehradun and the results obtained are highly satisfactory. This paper discusses the method used in developing these applications and efficacy and utility of both the applications in preparation of working plan and volume tables.